2021
DOI: 10.1186/s12891-021-04797-2
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-only debridement, internal fixation, and interbody fusion using titanium mesh in the surgical treatment of thoracolumbar tuberculosis with spinal epidural abscess: a minimum 5-year follow-up

Abstract: Objective To investigate the clinical efficacy and feasibility of posterior-only debridement, internal fixation, and interbody fusion using titanium mesh in the surgical treatment of thoracolumbar tuberculosis (TB) with spinal epidural abscess. Methods From January 2008 to January 2014, a total of 45 patients (27 male and 18 female) were reviewed. The patients were diagnosed with thoracolumbar TB with spinal epidural abscess. The patients underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…21-23 Luo et al 13 reported single-stage transpedicular decompression, debridement, posterior instrumentation, and fusion for thoracic STB with kyphosis and spinal cord compression in aged patients, all patients achieved solid fusion and significant kyphosis correction, and only 1 recurrence case. Gao et al 15 used posterior-only debridement, instrumentation, and interbody fusion using titanium mesh for thoracolumbar STB with epidural abscess, all patients achieved solid fusion, pain relief without pseudoarthrosis or implant failure, and the neurological score improved by 1 to 2 grades. By posterior debridement, bone graft, and instrumentation, the long transpedicular instrumentation can provide rigid 3-column fixation, immediate relief of pain due to spinal instability, and effective correction of kyphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21-23 Luo et al 13 reported single-stage transpedicular decompression, debridement, posterior instrumentation, and fusion for thoracic STB with kyphosis and spinal cord compression in aged patients, all patients achieved solid fusion and significant kyphosis correction, and only 1 recurrence case. Gao et al 15 used posterior-only debridement, instrumentation, and interbody fusion using titanium mesh for thoracolumbar STB with epidural abscess, all patients achieved solid fusion, pain relief without pseudoarthrosis or implant failure, and the neurological score improved by 1 to 2 grades. By posterior debridement, bone graft, and instrumentation, the long transpedicular instrumentation can provide rigid 3-column fixation, immediate relief of pain due to spinal instability, and effective correction of kyphosis.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recently, the single-posterior approach is increasingly popular in the surgical treatment of STB and exhibited promising effects as well as superior safety. [13][14][15] However, never had any study investigated the efficacy and safety of posterior-only debridement, osteotomy, correction, bone graft, and fusion in the treatment of recurrent thoracic/thoracolumbar STB with kyphosis. The aim of this study was to review our cases and analyze the feasibility of the posterior surgery in such circumstances and provide experiences for the development of STB treatment.…”
mentioning
confidence: 99%
“…To cope with the significant destruction to vertebrae and endplate, our team had adopted various measures to achieve anterior reconstruction including biocages/titanium mesh loaded with autograft particles, or allograft blocks with autograft particles according to individualized situations. As for large columnar defect after radical debridement, titanium mesh loaded with autograft particles was a standard option [ 34 ], which, however, would necessitate large amounts of autogenic resource from iliac crest with risk of donor site morbidity [ 35 ]. Therefore, besides titanium mesh and biocage applied in the study, an allograft block with autograft particles was also a common alternative we adopted to decrease the requirement of autograft.…”
Section: Discussionmentioning
confidence: 99%
“…123 In the past few years, with the popularity of the pedicle screw fixation system, the posterior approach has evolved as the mainstay for the surgical treatment of spinal tuberculosis and has shown satisfactory results. 125 A number of retrospective studies have illustrated that compared with the anterior approach, the posterior approach can reduce postoperative complications, decrease operative time and intraoperative blood loss, and often achieve better recovery results. 122,126 Also, for some advanced tuberculosis patients with severe kyphosis, good deformity correction can be accomplished by posterior osteotomy.…”
Section: Surgical Treatmentmentioning
confidence: 99%